Design Science: research in a theorical field - Carneiro, Luciana Emirena dos Santos (2019)
The present research maps the advances in the theoretical field of Design Science from a set of Brazilian works. The objective is to demonstrate from the study of one of the works a way of organizing the theoretical field in the context of Information Science, using the representation in a bibliometric map on the subject. A qualitative study is developed through a descriptive research that starts from a general premise about Design Science and adds intermediate or particular premises to the term. The data used to construct the research are composed by the universe of Brazilian theses that approached the subject or had the term Design Science present in the title of their works, and in addition a set of relevant Brazilian works on the theme that were available in the database of CAPES on the date of the consultation. The data collected from the literature review served as a reference for the analysis of a bibliometric map of a thesis on the subject, specially created with the function of representing the knowledge about the theme available in Brazilian theses, facilitating the consultative studies and the future research in the field of Design Science. Specifically, it is expected that the results with the research offer: a) description of the behavior of the term of Design Science, based on the works consulted, in view of its representativeness in several areas of knowledge; b) presentation of the term Design Science in a transdisciplinary perspective; c) representation of the knowledge about the thematic as a form of organization of the field.